2018
DOI: 10.1071/rd17472
|View full text |Cite
|
Sign up to set email alerts
|

New objective measurements of semen wave motion are associated with fertility in sheep

Abstract: In sheep, wave motion in semen is currently used by AI centres to select ejaculates for insemination. Despite its low cost, convenience and established ability to predict fertility, the subjectivity of this assessment is a limiting factor for its applicability. The aims of the present study were to establish an objective method for the analysis of wave motion and to assess the associations of objective parameters with fertility after cervical insemination. Collective sperm motion in undiluted semen was observe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…It has been reported that sperm motility is tightly associated with the results of AI [6][7][8] . Furthermore, seminal plasma plays a critical role in sperm motility regulation [9][10][11][12][13] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been reported that sperm motility is tightly associated with the results of AI [6][7][8] . Furthermore, seminal plasma plays a critical role in sperm motility regulation [9][10][11][12][13] .…”
Section: Discussionmentioning
confidence: 99%
“…Instantly after collecting, we counted volume of semen and observed semen color. Mass motility was rst assessed by observing the wave motion pattern of fresh undiluted semen 76,77 . However, the assessment of mass motility is subjectively carried out on the basis of the experience and knowledge of the technicians, so it is only a rough assessment.…”
Section: Animals and Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…Regardless of whether sperm populations demonstrate extreme hyper-or hypomethylation, there appears to consistently be a relationship with motility, suggesting that spermatozoa on either end of the methylation spectrum demonstrate impaired motility. Given that sperm motility is a key characteristic used to determine ejaculate fertility in the sheep production industry [69,70], external factors that alter motility are of interest. In this case, we cannot conclude upon any causation behind the relationship between global methylation and sperm motility but can speculate that this may partially be attributed to the other correlations revealed in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Instrumentation for CASA analysis has developed rapidly alongside our biological understanding, so we wanted to reflect some of this progress. One of the papers (David et al 2018) is interesting because it capitalises on some of the earliest observations made with ram semen; namely, that if an undiluted sample is viewed through a low powered objective, it is usually possible to see a great deal of swirling and wave motion. Although the early pioneers of sperm assessment developed rating systems to rank such sperm behaviour, a group of biologists and mathematicians has developed an unusual CASA approach that quantifies the wave motion to such a degree of accuracy that the data are predictive of AI success in sheep.…”
mentioning
confidence: 99%